Influência de fatores bióticos e abióticos no crescimento e reprodução da mirmecófita Miconia tococa (Desr.) Michelang. (Melastomataceae) - Belan, Helen Carla (2020)
Ant-plants, or myrmecophytes, have specialized structures that provide shelter to ants, such as domatia and hollow stems. Besides sheltering, these plants can also provide food resources in the form of extrafloral nectar. In exchange for these benefits, ants offer protection against herbivores and pathogens and can aid in plant nutrition. Several biotic and abiotic factors can affect this mutualism and the development of the organisms involved. I evaluated the effect of biotic and abiotic factors on the growth and reproduction of the myrmecophyte Miconia tococa (Melastomataceae). In the first chapter, I performed experiments to assess the relative importance of trophic mutualism and protection against herbivory in the interaction between M. tococa and the ant Allomerus octoarticulatus. Seedlings of M. tococa were subject to five treatments: (i) colonization by A. octoarticulatus, (ii) protection against herbivores, (iii) protection against herbivores and with fertilizer addition, (iv) fertilizer addition only, and (v) control. Both colonized plants and protected plants grew more than control plants or those submitted to artificially fertilized treatment, which indicates that protection against natural enemies is more important for the plant development than the nutritional support provided by ants. In the second chapter, I evaluated whether the presence of opportunistic ants in the reproductive structures of M. tococa affects its reproductive output. In inspecting anatomical traits, I found an epidermis filled with glandular trichomes that produce extranuptial nectar on M. tococa petals. The production of nectar occurred in the floral bud stage, and at least 17 ant species foraged on these buds without interfering with pollinator activity. Moreover, I used experiments to demonstrate that the presence of ants in the inflorescences increased the proportion of floral buds producing fruits by 15%. In the third chapter, I investigated how M. tococa respond to environments under different abiotic conditions. I assessed morphological and physiological traits, in addition to the palatability, growth, and reproduction of M. tococa individuals naturally present in environments with two levels of light: interior and edge of gallery forest. Plants in the forest edge had leaves with greater toughness, higher trichome density on the abaxial surface, and lower palatability than plants in the forest interior. In the absence of interactions with obligate ants, plants at the forest edge showed more active metabolism and greater production of photoassimilates, which resulted in a greater number of inflorescences relative to plants in the interior forest. In the presence of interactions with obligate ants, the environmental lightness did not affect plants reproductive output, which indicates that the mutualistic interaction reduces the vulnerability of the plants to variations in the abiotic conditions. Overall, I showed that biotic factors such as the presence of mutualistic ants, and abiotic factors as light intensity, both affect the development of the myrmecophyte M. tococa, and that the synergistic association among these different factors can affect the outcome of mutualistic interactions.